COVID-19 and Heart Diseases (Journal of Chittagong Medical College Teachers' Association, 2020)
Many patients with Coronavirus Disease 2019(COVID19) have pre-existing heart disease or develop various cardiac complications during the disease. This review article is aimed to design understanding the relationship between heart disease and COVID-19 is necessary for optimum management of such condition. Literature search done by using PubMed, Medline and Cochrane data bases. Heart involvement occurs in approximately 8-12% of all patients.Acute cardiac injury, as evident by a significant cardiac  troponin elevation is the commonest abnormality. Myocarditis, type II myocardial infarction, heart failure, arrhythmia are other cardiac manifestations that are less common.Pre-existing heart disease and/or involvement of the heart by COVID-19 carries worse prognosis. Most of the reports currently available describes cardiac manifesta- tions briefly. Further study may reveal more clearly the various aspects of cardiac manifestations in COVID-19 patients.JCMCTA 2020 ; 31 (2) : 3-9